General Anesthesia Versus Conscious Sedation and Local Anesthesia During Thrombectomy for Acute Ischemic Stroke. Issue 7 (July 2020) - Cappellari, Manuel; Pracucci, Giovanni; Forlivesi, Stefano; Saia, Valentina; Nappini, Sergio; Nencini, Patrizia; Inzitari, Domenico; Greco, Laura; Sallustio, Fabrizio; Vallone, Stefano; Bigliardi, Guido; Zini, Andrea; et al.
Abstract : Background and Purpose: As numerous questions remain about the best anesthetic strategy during thrombectomy, we assessed functional and radiological outcomes in stroke patients treated with thrombectomy in presence of general anesthesia (GA) versus conscious sedation (CS) and local anesthesia (LA). Methods: We conducted a cohort study on prospectively collected data from 4429 patients enrolled in the Italian Registry of Endovascular Treatment in Acute Stroke. Results: GA was used in 2013 patients, CS in 1285 patients, and LA in 1131 patients. The rates of 3-month modified Rankin Scale score of 0–1 were 32.7%, 33.7%, and 38.1% in the GA, CS, and LA groups: GA versus CS: odds ratios after adjustment for unbalanced variables (adjusted odds ratio [aOR]), 0.811 (95% CI, 0.602–1.091); and GA versus LA: aOR, 0.714 (95% CI, 0.515–0.990). The rates of modified Rankin Scale score of 0–2 were 42.5%, 46.6%, and 52.4% in the GA, CS, and LA groups: GA versus CS: aOR, 0.902 (95% CI, 0.689–1.180); and GA versus LA: aOR, 0.769 (95% CI, 0.566–0.998). The rates of 3-month death were 21.5%, 19.7%, and 14.8% in the GA, CS, and LA groups: GA versus CS: aOR, 0.872 (95% CI, 0.644–1.181); and GA versus LA: aOR, 1.235 (95% CI, 0.844–1.807). The rates of parenchymal hematoma were 9%, 12.6%, and 11.3% in the GA, CS, and LA groups: GA versus CS: aOR, 0.380 (95% CI, 0.262–0.551); and GA versus LA: aOR, 0.532 (95% CI, 0.337–0.838). After model of adjustment for predefined variables (age, sex, thrombolysis, National Institutes of Health Stroke Scale, onset-to-groin time, anterior large vessel occlusion, procedure time, prestroke modified Rankin Scale score of <1, antiplatelet, and anticoagulant), differences were found also between GA versus CS as regards modified Rankin Scale score of 0–2 (aOR, 0.659 [95% CI, 0.538–0.807]) and GA versus LA as regards death (aOR, 1.413 [95% CI, 1.095–1.823]). Conclusions: GA during thrombectomy was associated with worse 3-month functional outcomes, especially when compared with LA. The inclusion of an LA arm in future randomized clinical trials of anesthesia strategy is recommended. Abstract : Supplemental Digital Content is available in the text.